Changes in CD4+CD25HIGH T cells and TGFb1 levels in different stages of adult-onset type 1 diabetes - Miličić Tanja; Jotić Aleksandra; Marković Ivanka; Popadić Dušan; Lalić Katarina; Uskoković Veljko; Lukić Ljiljana; Maćešić Marija; Stanarčić Jelena; Stoiljković Milica; Milovančević Mina; Rafailović Đurđa; et al. (Journal of Medical Biochemistry)
Background: Previous studies suggested an important role of impairments in T cell subsets in different stages during type 1 diabetes (T1D) development, while data regarding CD25high T cells and transforming growth factor b1 (TGFb1), both T regulatory associated, remains controversial. We analyzed the level of (a) CD25high T cells (b) TGFb1 in 17 first-degree relatives of patients with T1D in stage 1 (FDRs1) (GADA+, IA-2+); 34 FDRs in stage 0 (FDRs0) (GADA, IA-2); 24 recent-onset T1D in insulin-requiring state (IRS); 10 patients in clinical remission (CR); 18 healthy, unrelated controls (CTR). Methods: T cell subsets were characterized by two-color immunofluorescence staining and flow cytometry; TGFb1 was determined by ELISA, GADA, and IA-2 by RIA. Results: The percentage of CD25high T cells in FDRs1 was lower than controls, FDRs0, IRS, and CR (p<0.001). Additionally, the cut-off value for CD25high = 1.19%, with a probability of 0.667, for having a higher risk for T1D. TGFb1 concentration in FDRs1, FDRs0, IRS, and CR, was lower than controls (p<0.001). IRS has a higher TGFb1 concentration than CR (p<0.001). Conclusions: Stage 1, a higher risk for T1D, is characterized by decreases in CD25high T cells and TGFb1, partially reflecting impaired T regulatory response, implying that changes of this T cells subset might be a risk marker for T1D. FDRs, irrespective of risk for T1D and T1D patients irrespective of state, had depletion of TGFb1, suggesting the association of TGFb1 could have potential with familiar risk and manifestation of T1D. Furthermore, the result suggested that the clinical course of overt T1D might be modulated on the TGFb1 level.